PEMBANGUNAN KAMUS BAHASA DAERAH KARO KE BAHASA INDONESIA DAN BAHASA INGGRIS PADA PERANGKAT MOBILE BERBASIS ANDROID - Bahagia Tarigan (UPPM, 2018)
Indonesia has a diverse daerah.Kamus language is one of the major media to introduce thelanguage and know the meaning in a particular language. The use of local languagedictionaries are generally obtained in a language translation. How can users vernaculartranslate into national and even international. In addition, smart phone technology advancedrapidly in the use of communication media at this time. Designing a multilingual dictionaryfor Android OS based regions permits as an alternative medium to translate the language.The test is performed by registering 500 vocabulary karo area, stored in file.txt on AndroidStudio is done. Experiments show that the Dictionary application functions correctly..